Aplicação de métodos voltamétricos de análise na especiação de cromo, selênio e antimônio em matrizes salinas - Jost, Cristiane Luisa (2010)
This work aimed to explore the speciation analysis of chromium, selenium and antimony, elements of clinical and geochemical relevance, in the saline samples seawater, hydrothermal fluid and hemodialysis fluid. These samples, although linked to different research areas, have many similarities relating to their chemical compositions or the presence of metallic species as contaminants as well as major components. Voltammetric methods were used to the determination of the analytes in high salt media without the use of dilution, masking agents or separation steps. Since changes in the matrix composition may affect the analyte peak current magnitude, factors affecting the voltammetric behavior of the species related to sample composition (e.g., presence of dissolved organic matter and ionic strength) were evaluated. The chromium speciation analysis was performed by the adsorptive collection of the Cr-DTPA complex on the mercury working electrode, followed by stripping in combination to a catalytic step. Cr(III) species was found as predominant in the hydrothermal fluid sample and, Cr(VI), in the seawater sample, whereas in hemodialysis fluids an ignorable concentration was determined. Selenium was determined by the co-electrolysis of Cu2Se followed by a cathodic stripping in acidic medium. The UV-irradiation pre-treatment step was used for the reductively conversion of non-electroactive species into Se(IV) as well as for dissolved organic matter photo-oxidation, and the speciation was applied to the real sample analysis, where no selenium species were found. The combined use of adsorptive and anodic stripping voltammetry was employed for antimony determination. Chloranilic acid was chosen as the Sb(III) complex forming reagent (pH 3.0) and the total antimony concentration was evaluated by anodic stripping voltammetry in a 5.0 mol L-1 HCl medium. Sb(III) was found as the predominant species in the hydrothermal fluid sample, whereas Sb(V) is predominant in the seawater sample. No antimony species were found in the hemodialysis fluid. Concerning chromium, selenium and antimony species, remarkable peak current dependences on peak potential, deposition potential, deposition time and scan rate were observed for all investigated media. The limit of detection values were appropriate to the analytes determination, so that the present techniques consist in simple, fast and low cost procedures for the speciation analysis of elements of clinical and geochemical relevance in high salt content samples with accuracy and sensitivity.